(untitled) (Baghdad Science Journal, 2013)
Novel heterocyclic polyimide 5(a,b) have been synthesized based on polyacrylic backbone. The synthetic route start with nucleophilic substitution of 2-amino, or 4-amino, pyridine 1(a,b) to the polyacryloyl chloride afforded poly substituted amide 2(a,b). Another nucleophilic substitution were carried with adipoyl chloride to form polyimide chloride 3(a,b). Treatment of 3(a,b) with hydrazine hydrate afforded acid hydrazide polyimide 4(a,b), which upon cyclocondensation with carbon disulfide gave the target heterocyclic polyimide. The synthesized compounds were identified by spectroscopic methods: FT-IR, 1H-NMR and 13C-NMR.